Yield and Development of Citrullus lanatus Thunb., with Plastic Mulch and Vermicompost as a Nutritional Source - Moreno-Reséndez, Alejandro; Reyes-Carrillo, José Luis; López-Salazar, Rubén; Espinoza-Banda, Armando; Márquez-Guerrero, Selenne Yuridia (REVISTA TERRA LATINOAMERICANA, 2024)
In dif ferent trials have shown that the use of both vermicompost (VC) and plastic mulch has favored the yield and productivity of a large number of crops. The purpose of our study was to compare synthetic fertilization vs the incorporation of VC on the development of triploid watermelon with plastic mulch in the spring-summer 2019 agricultural cycle at the experimental field of the Universidad Autónoma Agraria Antonio Narro. The treatments evaluated, each with three repetitions, were: exploratory application of VC, at a rate of 30 and 60 Mg ha-1, and as a control, the regional recommendation 240-120-00 ha-1 (N-P-K). The sowing was carried out in planting beds of 2 × 8 m (width and length, respectively) covered with black plastic. The sowing of the triploid watermelon seeds of the Crunchy Red variety, was carried out in Styrofoam trays with 200 cavities filled with Peat Moss. When the seedlings had two to three true leaves, they were transplanted 1.0 m apart on planting beds of 2 × 8 m (width and length, respectively) covered with black plastic. For the supply of water, drip irrigation was used. To evaluate the ef fect of the treatments, a completely randomized experimental design was used, the DMS0.05 test was applied for comparisons of the means. Due to the ef fect of the treatments evaluated, five of the variables studied: equatorial and polar diameters, pulp thickness, soluble solids and fruit weight presented highly significant dif ferences, while yield registered a significant dif ference. The highest yield of 29 932 Mg ha-1 was recorded with the incorporation of 60 Mg ha-1 of VC confirming that this natural fertilizer was able to satisfy the nutritional needs of triploid watermelon without synthetic fertilization.